1998
DOI: 10.1007/bf02744940
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton and polyploidy after maturation and fertilization of cryopreserved germinal vesicle—stage mouse oocytes

Abstract: Purpose: Our purpose was to assess the effect of cryopreservation on cytoskeleton of germinal vesicle (GV) mouse oocytes and determine whether irreversible spindle damage and related digyny associated with cryopreservation of metaphase H (MII (96, 94, and 37%, respectively) and control (98, 97, and 45%, respectively)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 23 publications
1
21
1
1
Order By: Relevance
“…Oocyte cryopreservation at the GV stage seems to be particularly advantageous to circumvent the spindle damage, because increased digyny often experienced after cryopreservation of M-II stage oocytes [65]. In pigs, because of low survival rates, cryopreservation of immature oocytes such as at the GV stage gained little interest so far.…”
Section: Immature Oocytes; Low Survival But the Developmental Abilitymentioning
confidence: 99%
“…Oocyte cryopreservation at the GV stage seems to be particularly advantageous to circumvent the spindle damage, because increased digyny often experienced after cryopreservation of M-II stage oocytes [65]. In pigs, because of low survival rates, cryopreservation of immature oocytes such as at the GV stage gained little interest so far.…”
Section: Immature Oocytes; Low Survival But the Developmental Abilitymentioning
confidence: 99%
“…In the limited studies that have been done in the mouse, it has been shown that GV-stage oocytes can be successfully frozen and thawed [31][32][33], that they can subsequently mature in culture and form morphologically normal spindles [33], and that they can develop after fertilization and produce live births [31,32]. However, as in bovine oocytes, the developmental competence in terms of blastocyst formation and live births is approximately 50% lower than that of unfrozen controls [31,32].…”
Section: Introductionmentioning
confidence: 97%
“…In pigs, it has been confirmed that mature (MII stage) oocytes have higher survival ability during cryopreservation than immature oocytes [21]. On the other hand, cryopreservation of matured mammalian oocytes has been associated with damage of the meiotic spindle and actin microfilaments [2,3,11,19], causing the failure of second polar body (2PB) extrusion and the possible generation of embryos with abnormal numbers of chromosomes [2,6,7]. Cytoskeletal elements are known to regulate several events during fertilization in mammalian oocytes such as sperm penetration and 2PB extrusion [25,26].…”
mentioning
confidence: 98%